Optimizing the Use of Electrical Energy in Urban Communities Through The Listrik BENAR Application Socialization: Optimalisasi Penggunaan Energi Listrik pada Masyarakat Kota Melalui Sosialisasi Aplikasi Listrik BENAR - Eddy Lybrech Talakua; Mahesa Sangga Bhuana; Nur Kurniasari; Erwin Dhaniswara; Tamaji (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Electrical energy is a primary need for all levels of society today. In the city of Surabaya, the level of electrical energy demand is increasing. The government, through the State Electricity Company (PLN), continues to strive to meet this need and provide the best service in distributing electrical energy so that it reaches consumers properly and safely. In the community, there is still misuse of electrical energy that can cause fires, wasted electrical power due to technical errors, and the use of substandard electrical materials. This is the basis for providing insight and knowledge to the public about the BENAR electrical installation techniques (Baik, Efektif, Nyaman, Aman, and Rapi) to the community. This community service program was carried out for four days (September 27-30, 2025) starting from a pre-test, presentation of material on the introduction and use of electrical energy, and socialization of the BENAR Electricity Application. Participants also practiced electrical installations using the provided practice modules. From the post-test results, it appears that the level of public understanding and awareness of electrical energy use has increased significantly. With a community of electricity users who have insight and knowledge about electrical energy, disasters caused by the misuse of electrical energy can be reduced and prevented.